2022
DOI: 10.1007/s11845-022-03238-w
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between tele-assessment and face-to-face assessment of 30-s sit-to-stand test in patients with type 2 diabetes mellitus

Abstract: Background The globalization of healthcare systems, and the aim to lower healthcare costs have all contributed to the growth of telehealth technology in recent years. However, before these systems are put into use, their efficacy should be verified. To the best of our knowledge, this is the first study focusing on the evaluation of functional exercise capacity using the 30-s sit-to-stand (30-s STS) test as a tele-assessment method in patients with type 2 diabetes mellitus (T2DM). Aims The purpose of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Faceto-face assessment and tele-assessment were doing with WhatsApp application by different physiotherapists. This study revealed that although physiotherapists used different assessment methods, there was no difference between the results (27). In additionally, Mani et al showed that Tele-rehabilitation based assessments were valid and reliable for the neck pain intensity, active range of motion, deep neck flexor muscle endurance and disability with using computer program.…”
Section: Discussionmentioning
confidence: 75%
“…Faceto-face assessment and tele-assessment were doing with WhatsApp application by different physiotherapists. This study revealed that although physiotherapists used different assessment methods, there was no difference between the results (27). In additionally, Mani et al showed that Tele-rehabilitation based assessments were valid and reliable for the neck pain intensity, active range of motion, deep neck flexor muscle endurance and disability with using computer program.…”
Section: Discussionmentioning
confidence: 75%